Body temperature increases during pediatric full mouth rehabilitation surgery under general anesthesia - Yi-Shan Chuang; Chung-Hsing Li; Chen-Hwan Cherng (Elsevier, 2015)
Background/purpose: General anesthesia is necessary for full mouth rehabilitation surgery in children. Pediatric patients are susceptible to developing hypothermia during surgery under general anesthesia. This study reports gradually increased body temperature in pediatric patients receiving full mouth rehabilitation surgery. Materials and methods: Following institutional review board approval, the medical records of pediatric patients who received full mouth rehabilitation surgery from 2011 through 2012 were collected. The body temperatures (preoperative, periodic during operation, and postoperative 5 hours and 12 hours) and the maximum differences in temperature change during operation were recorded. Results: A total of 34 patients were enrolled in this study. An increase in body temperature was found. The mean ± standard deviation of the difference in temperature change was found to be 2.50 ± 1.17°C. A significant positive correlation was noted (r = 0.464, P = 0.006) between the maximum temperature changes and the operation duration. At 12 hours after operation, no patients were reported to have a tympanic temperature >37.5°C. Conclusion: Body temperature transiently increased during pediatric full mouth rehabilitation surgery. The increase in body temperature was associated with operation duration. The etiology is uncertain. Continuous body temperature monitoring and the application of both heating and cooling devices during pediatric full mouth rehabilitation surgery should be mandatory.